Unexpected Higher-Order Effects in Charged Particle Impact Ionization at High Energies - Foster, M.; Peacher, J. L.; Schulz, M.; Madison, D. H.; Chen, Zhangjin; Walters, H. R. J. (My University, 2006)
Most of the experimental and theoretical studies of electron-impact ionization of atoms, referred to as (e, 2e), have concentrated on the scattering plane. The assumption has been that all the important physical effects will be observable in the scattering plane. However, very recently it has been shown that, for C6+-helium ionization, experiment and theory are in nice agreement in the scattering plane and in very bad agreement out of the scattering plane. This lack of agreement between experiment and theory has been explained in terms of higher-order scattering effects between the projectile and target ion. We have examined electron-impact ionization of magnesium and have observed similar higher-order effects. The results of the electron-impact ionization of magnesium indicate the possible deficiencies in the calculation of fully differential cross sections in previous heavy particle ionization work.